Access to hands-on mathematics measurement activities using robots controlled via speech generating devices: three case studies. (July 2014) - Adams, Kim; Cook, Al
Abstract Purpose: To examine how using a robot controlled via a speech generating device (SGD) influences the ways students with physical and communication limitations can demonstrate their knowledge in math measurement activities. Method: Three children with severe physical disabilities and complex communication needs used the robot and SGD system to perform four math measurement lessons in comparing, sorting and ordering objects. The performance of the participants was measured and the process of using the system was described in terms of manipulation and communication events. Stakeholder opinions were solicited regarding robot use. Results: Robot use revealed some gaps in the procedural knowledge of the participants. Access to both the robot and SGD was shown to provide several benefits. Stakeholders thought the intervention was important and feasible for a classroom environment. Conclusions: The participants were able to participate actively in the hands-on and communicative measurement activities and thus meet the demands of current math instruction methods. Implications for Rehabilitation Current mathematics pedagogy encourages doing hands-on activities while communicating about concepts. Adapted Lego robots enabled children with severe physical disabilities to perform hands-on length measurement activities. Controlling the robots from speech generating devices (SGD) enabled the children, who also had complex communication needs, to reflect and report on results during the activities. By using the robots combined with SGDs, children both exhibited their knowledge of and experienced the concepts of mathematical measurements.